Ethnopharmacological Study of Medicinal Plants in Kedungpoh Village, Nglipar Sub-district, Gunungkidul District, Special Region of Yogyakarta - Untari, Ludmilla Fitri; Vidhantyka, K.H. Mahadhevy Ryrathna; Ananmaimuna, Jovika Syifa; Nilamsari, Regina; Malika, Pradhika Cikal; Poerwanto, Soenarwan Hery; Siswanti, Dwi Umi; Purwanto, Hari (Journal of Biotechnology and Natural Science, 2025)
The scientific study of ethnopharmacology investigates the medicinal uses of plants by different ethnic groups and plays a crucial role in the early-stage drug discovery process by identifying potential drug candidates from traditional remedies. The transmission of knowledge concerning the diversity of plant species and their utilization is typically an intergenerational process, facilitating the preservation of cultural heritage and the transfer of experiential knowledge. The present study was conducted in the village of Kedungpoh, Nglipar, Gunungkidul. The objective of this study is to investigate the utilisation, management and comprehension of medicinal plants within the Kedungpoh village in Gunungkidul.The research methodology comprised of observational studies and interviews with local residents. The results revealed the utilization of 24 plant species, which classified into 17 distinct families by the local community. The utilization of these plants encompassed various plant organs, including leaves, stems, roots, fruits, and rhizomes, which were employed in different processing methods, such as crushing, boiling, or rubed. The most prevalent and utilized plant families were Asteraceae, which are notable for their abundance of bioactive compounds, including flavonoids, alkaloids, and essential oils, which have been demonstrated to be efficacious in addressing a wide range of health concerns. This study provides substantial support for scientific laboratory research into the safety, quality and efficacy of traditional medicine practices, with a view to further utilization of traditional medicine, whilst also protecting the intellectual property rights of traditional knowledge holders.